Pigmentation and growth-temperature response of Phytophthora meadii and P. nicotianae var. nicotianae infecting cardamom (Elettaria cardamomum Maton) - Sarma, R Suseela Bhai, Y R (Journal of Spices and Aromatic Crops, 2003)
Capsule rot (’Azhukal’) and leaf blight are two major Phytophthora diseases of small cardamom (EZettaria cardamom Maton). Variability among the Phytophthora isolates causing these diseases were studied using Phytophthora cultures isolated from rot affected plant parts such as capsules, rhizomes, leaf and also from blight affected leaves collected from different locations. Detailed studies on growth of these cultures in different media and at different temperatures showed significant difference between these’ isolates. P. meadii did not cause any pigmentation in casein hydrolysate tyrosine agar (Timmer’s medium) and the fungus did not grow at high lemperature while P. nicotianae var. nicotianae showed chocolate reddish brown pigmentation in casein hydrolysate tyrosine agar and did grew at high temperature. Therefore pigmentation in casein hydrolysate tyrosine agar and growth at high temperature were found ideal for differentiating Phytophthora isolates infecting cardamom.